The Feasibility of Saga Text Teaching Materials Utilizing a Website for Assignments and Resources in Class X at Azizi Islamic Senior High School - Nduru, Muhammad Zulfadlan; Ali, Ali; Rita, Rita (Indonesian Journal of Education Research (IJoER), 2025)
Purpose of the study: This study aims to develop, assess the feasibility, and evaluate the effectiveness of saga text teaching materials utilizing a website as a platform for assignments and resources for Class X students at Azizi Islamic Senior High School. Methodology: This study employs a Research and Development (R&D) approach using the 4D model by Thiagarajan, consisting of Define, Design, Development, and Dissemination stages. The research methods include qualitative and quantitative approaches. Data were collected through observations, interviews, and questionnaires, with material experts, media experts, teachers, and students serving as evaluators. The study uses a saturated sampling technique, involving 18 students from Class X. Main Findings: The feasibility assessment categorized the saga text teaching materials as "very appropriate." The validity assessment from material experts resulted in 95%, while media experts rated it 87%, both categorized as "very decent." Teachers provided an evaluation score of 93%, and students rated it 91.22%, indicating positive responses. Student learning outcomes reached 91%, categorized as "very effective." Novelty/Originality of this study: This study introduces a website-based teaching material approach tailored for saga text learning, enhancing student engagement and independent learning. Unlike conventional printed materials, this method integrates digital interactivity with real-time assignment submission, making it a modern and adaptive educational resource for literature instruction.